2022
DOI: 10.1088/1674-4926/43/3/034102
|View full text |Cite
|
Sign up to set email alerts
|

Performance enhancement of solution-processed InZnO thin-film transistors by Al doping and surface passivation

Abstract: Solution-processed oxide semiconductors have been considered as a potential alternative to vacuum-based ones in printable electronics. However, despite spin-coated InZnO (IZO) thin-film transistors (TFTs) have shown a relatively high mobility, the lack of carrier suppressor and the high sensitivity to oxygen and water molecules in ambient air make them potentially suffer issues of poor stability. In this work, Al is used as the third cation doping element to study the effects on the electrical, optoelectronic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The electronegativity difference between Al (1.5) and O (3.5) was larger than that between Al and Sn (1.8), causing Al 3+ ions to have a stronger bond with O 2− than with Sn 4+ ions. 42 The added Al successfully decreased the number of oxygen vacancies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electronegativity difference between Al (1.5) and O (3.5) was larger than that between Al and Sn (1.8), causing Al 3+ ions to have a stronger bond with O 2− than with Sn 4+ ions. 42 The added Al successfully decreased the number of oxygen vacancies.…”
Section: Resultsmentioning
confidence: 99%
“…The deposited Al layers were fully converted to Al 2 O 3 and the partially diffused Al 3+ functioned as an effective suppressor of VO formation. The electronegativity difference between Al (1.5) and O (3.5) was larger than that between Al and Sn (1.8), causing Al 3+ ions to have a stronger bond with O 2– than with Sn 4+ ions . The added Al successfully decreased the number of oxygen vacancies.…”
Section: Resultsmentioning
confidence: 99%
“…This method can solve the supercycle problem, where multilayer materials are created where the binary materials are not mixed uniformly. The elemental composition of the multicomponent thin film can be finely controlled through the injection pressure of the coinjected precursor . However, when depositing thin films using a codosing approach, unless the partial pressure of the precursor gas is perfectly homogeneous, deposition of films of uniform composition in complex nanostructures such as trenches is not possible.…”
Section: Ald For Film Growth Of Multicomponent Oxide Semiconductorsmentioning
confidence: 99%
“…The elemental composition of the multicomponent thin film can be finely controlled through the injection pressure of the coinjected precursor. 38 However, when depositing thin films using a codosing approach, unless the partial pressure of the precursor gas is perfectly homogeneous, deposition of films of uniform composition in complex nanostructures such as trenches is not possible. In the case of codosing thin films, uniform surface adsorption of both precursors is required to create a thin film with a uniform composition, so it is mainly used on spatial ALD on flat wafers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several types of double-layered TCO were reported by several institutes, such as AZO+ITO, AZO+antimony doped tin oxide (ATO), and ZnO+ITO [11,13], so the feasibility of the SHJ solar cells with an additional TCO+ITO should be studied for the commercialization of SHJ solar cells. Zinc-doped indium oxide (IZO) has been intensively studied as transistor and TCO resulting from its high mobility and low resistivity [14][15][16][17][18]. M. Morales-Masis reported that SHJ solar cells with IZO showed a significant improvement of Jsc, which achieved an efficiency above 21.5% [14].…”
Section: Introductionmentioning
confidence: 99%